Pyrrolysyl‐tRNA synthetase variants reveal ancestral aminoacylation function. Issue 19 (28th August 2013) - Ko, Jae-hyeong; Wang, Yane-Shih; Nakamura, Akiyoshi; Guo, Li-Tao; Söll, Dieter; Umehara, Takuya
Abstract : Pyrrolysyl‐tRNA synthetase (PylRS) is a class IIc aminoacyl‐tRNA synthetase that is related to phenylalanyl‐tRNA synthetase (PheRS). Genetic selection provided PylRS variants with a broad range of specificity for diverse non‐canonical amino acids (ncAAs). One variant is a specific phenylalanine‐incorporating enzyme. Structural models of the PylRSamino acid complex show that the small pocket size and π‐interaction play an important role in specific recognition of Phe and the engineered PylRS active site resembles that of Escherichia coli PheRS. Abstract : Molecular evolution of PylRS reveals the ancestral PheRS activity. Superfolder GFP reporter enables rapid analysis of PylRS substrate specificity. The pocket size is critical to Phe recognition and rejection of Phe analogs.